Formative Assessment Instrument to Enhance Teachers' Information Literacy Skills Based on the DIKW Theory - Budi Manfaat; Herny Novianti (Journal of General Education and Humanities, 2025)
This study explores the integration of the DIKW (Data, Information, Knowledge, Wisdom) framework into formative assessment practices to enhance teachers' information literacy skills. Utilizing a design-based research (DBR) methodology, we developed and tested a formative assessment instrument specifically aimed at improving teachers' competencies in navigating and utilizing information effectively. The research investigates how the DIKW model can scaffold specific dimensions of information literacy, including critical evaluation of information sources, effective synthesis of information, and practical application of knowledge in teaching contexts. Additionally, the study examines teachers' perceptions of the effectiveness of the formative assessment instrument designed based on the DIKW framework. Findings indicate that the integration of the DIKW framework not only boosts teachers' confidence and competence in managing information but also enriches their instructional practices. This research contributes to the ongoing discourse on professional development in education, emphasizing the importance of reflective practices and structured assessment tools in fostering effective teaching and learning environments.